Sistem Informasi Screening Penerimaan Karyawan Baru pada PT. Adhirajasa Wirakencana Berbasis Web dengan Metode Simple Additive Weighting - Rohmat Pulou Arifin; Dwi Lestari; Raditya Galih Whendasmoro (FIKOM - Bung Karno University, 2023)
Screening of new employee data is an important activity that is directly related to the process of finding qualified employees. If this activity is done manually, it will be easy for human errors to occur and will also take a long time. At PT. Adhira Jasa Wirakencana HRD is still carrying out data screening activities in a semi-computerized manner, causing data to be missed for screening and also taking a long time besides the absence of a decision support system (SPK) such as Simple Additive Weighting (SAW) by assigning weights to 4 different factors. used are age, distance of residence, education and also work experience which causes screening to be less effective. To deal with all existing problems, an information system for screening data on new employee acceptance was made using the WEB-based Simple Additive Weighting (SAW) method using 4 criteria, namely age, distance of residence, education and work experience. This system uses MySQL as the database and PHP as the programming language.